2010
DOI: 10.3233/fi-2010-261
|View full text |Cite
|
Sign up to set email alerts
|

Game Solution, Epistemic Dynamics and Fixed-Point Logics

Abstract: Current methods for solving games embody a form of "procedural rationality" that invites logical analysis in its own right. This paper is a brief case study of Backward Induction for extensive games, replacing earlier static logical definitions by stepwise dynamic ones. We consider a number of analysis from recent years that look different conceptually, and find that they are all mathematically equivalent. This shows how an abstract logical perspective can bring out basic invariant structure in games. We then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Recursive solution procedures naturally correspond to definitions in existing fixed-point logics, such as the widely used system LFP(FO). An LFP(FO) formula mirroring the recursive nature of BI is constructed in [4,6] to define the classical BI relation, based on the above property RAT. Now, we have shown that sight-restricted SCBI, too, is a recursive game solution procedure.…”
Section: Solution Procedures and Fixed-point Logicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recursive solution procedures naturally correspond to definitions in existing fixed-point logics, such as the widely used system LFP(FO). An LFP(FO) formula mirroring the recursive nature of BI is constructed in [4,6] to define the classical BI relation, based on the above property RAT. Now, we have shown that sight-restricted SCBI, too, is a recursive game solution procedure.…”
Section: Solution Procedures and Fixed-point Logicsmentioning
confidence: 99%
“…Therefore, we know that M satisfies RATS. P However, compared with the generic logic in [4,3,2], the given definition in our logic is local. It is obvious that CF, the formula defining the property RAT, is insensitive to models -while our CFS M relies on a given model for its ranges of big disjunctions and conjunctions, and in its model-dependent notations like s(h) and h 1 ≥ h 2 .…”
mentioning
confidence: 99%
“…For a model M and a formula ϕ, we define the announcement limit lim ϕ M as the first model which is reached by successive announcements of ϕ that no longer changes after the last announcement is made. Announcement limits exist in both finite and infinite models (van Benthem & Gheerbrant, 2010). For instance, for any model M , lim p M = M |p for propositional variable p. Therefore, the limit model is the first updated model when the announcement is a ground Boolean formula.…”
Section: Announcement Stabilizationmentioning
confidence: 99%
“…The game-theoretical approach to the centipede game was initiated by Rosenthal [21], which was followed by several solution methods [2,13]. More recently, the role of rationality in its solution methods has been discussed [3,6] and extended to some other cases [16].The role knowledge as opposed to beliefs has been discussed in similar contexts by Artemov [1]. Moreover, based on experimental work, Ghosh, Meijering and Verbrugge aim to observe how humans reason strategically [11].…”
Section: Related Work and Conclusionmentioning
confidence: 99%